Amyloidosis in Alzheimer's Disease: The Toxicity of Amyloid Beta (Aβ), Mechanisms of Its Accumulation and Implications of Medicinal Plants for Therapy. (15th May 2013) - Prasansuklab, Anchalee; Tencomnao, Tewin
Abstract : Alzheimer's disease (AD) is a progressive neurodegenerative disorder that leads to memory deficits and death. While the number of individuals with AD is rising each year due to the longer life expectancy worldwide, current therapy can only somewhat relieve the symptoms of AD. There is no proven medication to cure or prevent the disease, possibly due to a lack of knowledge regarding the molecular mechanisms underlying disease pathogenesis. Most previous studies have accepted the "amyloid hypothesis, " in which the neuropathogenesis of AD is believed to be triggered by the accumulation of the toxic amyloid beta (A β ) protein in the central nervous system (CNS). Lately, knowledge that may be critical to unraveling the hidden pathogenic pathway of AD has been revealed. This review concentrates on the toxicity of A β and the mechanism of accumulation of this toxic protein in the brain of individuals with AD and also summarizes recent advances in the study of these accumulation mechanisms together with the role of herbal medicines that could facilitate the development of more effective therapeutic and preventive strategies.